Feasibility of Perflutren Microsphere Contrast Transthoracic Echocardiography in the Visualization of Ventricular Endocardium during Venovenous Extracorporeal Membrane Oxygenation in a Validated Ovine Model. Issue 3 (24th July 2014) - Platts, David G.; Diab, Sara; Dunster, Kimble R.; Shekar, Kiran; Burstow, Darryl J.; Sim, Beatrice; Tunbridge, Matthew; McDonald, Charles; Chemonges, Saul; Chan, Jonathan; Fraser, John F.
<x xml:space="preserve">Abstract</x> Background Transthoracic echocardiography (TTE) during extra corporeal membrane oxygenation (ECMO) is important but can be technically challenging. Contrast‐specific TTE can improve imaging in suboptimal studies. These contrast microspheres are hydrodynamically labile structures. This study assessed the feasibility of contrast echocardiography (CE) during venovenous (VV) ECMO in a validated ovine model. Method Twenty‐four sheep were commenced on VV ECMO. Parasternal long‐axis (Plax) and short‐axis (Psax) views were obtained pre‐ and postcontrast while on VV ECMO. Endocardial definition scores (EDS) per segment were graded: 1 = good, 2 = suboptimal 3 = not seen. Endocardial border definition score index (EBDSI) was calculated for each view. Endocardial length (EL) in the Plax view for the left ventricle (LV) and right ventricle (RV) was measured. Results Summation EDS data for the LV and RV for unenhanced TTE (UE) versus CE TTE imaging: EDS 1 = 289 versus 346, EDS 2 = 38 versus 10, EDS 3 = 33 versus 4, respectively. Wilcoxon matched‐pairs rank‐sign tests showed a significant ranking difference (improvement) pre‐ and postcontrast for the LV (P < 0.0001), RV (P < 0.0001) and combined ventricular data (P < 0.0001). EBDSI for CE TTE was significantly lower than UE TTE for the LV (1.05 ± 0.17 vs. 1.22 ± 0.38, P = 0.0004) and RV (1.06 ± 0.22 vs. 1.42 ± 0.47, P = 0.0.0006) respectively. Visualized EL was significantly longer in CE versus UE for both the LV (58.6 ± 11.0 mm vs. 47.4 ± 11.7 mm, P < 0.0001) and the RV (52.3 ± 8.6 mm vs. 36.0 ± 13.1 mm, P < 0.0001), respectively. Conclusions Despite exposure to destructive hydrodynamic forces, CE is a feasible technique in an ovine ECMO model. CE results in significantly improved EDS and increased EL.